2016
DOI: 10.1186/s12913-016-1804-9
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of microscopic observation drug susceptibility test versus Xpert MTB/Rif test for diagnosis of pulmonary tuberculosis in HIV patients in Uganda

Abstract: BackgroundMicroscopic Observation Drug Susceptibility (MODS) and Xpert MTB/Rif (Xpert) are highly sensitive tests for diagnosis of pulmonary tuberculosis (PTB). This study evaluated the cost effectiveness of utilizing MODS versus Xpert for diagnosis of active pulmonary TB in HIV infected patients in Uganda.MethodsA decision analysis model comparing MODS versus Xpert for TB diagnosis was used. Costs were estimated by measuring and valuing relevant resources required to perform the MODS and Xpert tests. Diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 44 publications
3
17
1
Order By: Relevance
“…Moreover, the study result indicated that if the cost of cartridge reduced by 10%, the unit cost would reduce by 9.75% below the base case. This estimate was similar to a study conducted in South Africa (47%) [19] and Uganda [27] that indicated the most of the costs of GeneXpert were attributed to the high price of the cartridge. This estimate shows that the high cost of cartridges can be the major obstacle to the full implementation of the diagnostic method as a routine test.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, the study result indicated that if the cost of cartridge reduced by 10%, the unit cost would reduce by 9.75% below the base case. This estimate was similar to a study conducted in South Africa (47%) [19] and Uganda [27] that indicated the most of the costs of GeneXpert were attributed to the high price of the cartridge. This estimate shows that the high cost of cartridges can be the major obstacle to the full implementation of the diagnostic method as a routine test.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, this study's result was consistent with a study done in South Africa [34] that found that using a novel diagnostic test (GeneXpert) for TB diagnosis was cost-saving and cost-effective. However, this nding contradicted the study in Uganda that found GeneXpert was not cost-effective [27]. This difference might be due to the algorithm compared with GeneXpert as MODS has almost similar diagnostic accuracy and low cost compared with the GeneXpert diagnostic method.…”
Section: Discussionmentioning
confidence: 65%
“…Cost-effectiveness acceptability curves (CEACs) were included in both articles [25,26], using the net benefit regression framework [36]. The reduction in antibiotic prescriptions was expressed in monetary terms 1 (50%) [87] 2 (29%) [89,90] (33%) [98] Middle income 5 (42%) [29,[32][33][34][35] 9 (20%) [38,43,55,58,64,71,75,79,84] 0 (0%) 2 (29%) [92,94] (67%) [96,97] Low income 1 (8%) [35] 5 (11%) [38,[44][45][46]83] 0 (0%) 1 (14%) [93] (33%) [98] as additional costs per patient prescription avoided [25] or additional costs per percentage reduction in antibiotic prescriptions [26]. Nicholson et al conducted a randomised controlled trial and health-economic evaluation of diagnostic tests for influenza, respiratory syncytial virus (RSV) and Streptococcus pneumoniae in adults hospitalised for chronic or acute cardiopulmonary illness in the UK [24].…”
Section: Regression Models and Trial-based Analysesmentioning
confidence: 99%
“…The main diagnostic test to detect TB was the Xpert test [38][39][40][41][42][43][44][45], with other articles assessing the lateral flow urine lipoarabinomannan assay Alere Determine™ test [46], the IGRA (Interferon-Gamma Release Assay) test [47] and the T-cell detection test [48]. The target population consisted of patients presenting with symptoms of active pulmonary TB disease [38][39][40][41][42][43]47], in some cases, patients with human immunodeficiency virus specifically [44][45][46]48]. The comparators were sputum smear microscopy [38][39][40][41]45], culture [42][43][44] and chest radiography [41,43,45].…”
Section: Decision Treesmentioning
confidence: 99%
See 1 more Smart Citation